Advances in the regulation mechanism of sugar and acid metabolism in peach fruit - LI Junhao; GE Xiaolan; ZHU Jie; BAI Ruixia; WANG Yuehui (Guoshu xuebao)
Peach (Prunus persica L.) is an economically important fruit crop in global commerce, and its special ‘peach flavor’ attracts many consumers. The soluble sugars and organic acids together determine the flavor quality of peach fruits and they are the main attributes that affect consumer satisfaction with the fruits. Therefore, the improvement of the flavor quality represents a crucial aspect for promoting consumption. In this paper, we firstly reviewed the accumulation characteristics of sugar-acid components in the fruits, their synthesis and catabolism, as well as the mechanism of transport. The main soluble sugars in the fruit include sucrose, fructose, glucose and sorbitol, and most of peach varieties are the type of sucrose-accumulating. During the development of fruit, the total sugar content of pulp increases continuously, and the sucrose content firstly shows an increasing trend, and then decreases in the late ripening period. The content of fructose and glucose shows a decreasing trend with fruit development. The content of sorbitol in the fruit is low, it increases firstly and then decreases with fruit development. The organic acids in the fruit mainly include malic acid, quinic acid and citric acid. Most varieties are the type of malic acid accumulation pattern. The organic acid content shows a decreasing trend during the development of the fruit. There are two trends of malic acid with the development of the fruits among different varieties, and they overall showed downward trend and slow accumulation trend, while the quinic acid and citric acid show overall downward trend. Secondly, the factors affecting the accumulation of sugar-acid in the fruit and their potential molecular regulatory mechanisms were summarized. Several enzyme-related genes encoding sugar synthesis, catabolism and transportation have been identified, such as the PpSUSs, PpSPSs, PpINVs, PpHXKs, PpHKLs, PpS6PDHs, PpSDH, PpSU-Ts, PpTSTs, PpSWEETs, PpSOTs and PpERDL16. With peach fruit development, only the expression level of the PpSUS4 is significantly correlated with the sugar content. Researchers have found that the PpNAINV2 regulates the sucrose metabolism in the postharvest fruit and its function is regulated by the invertase inhibitor gene PpINH1. Several enzyme-related genes encoding organic acid synthesis, catabolism and transport have been identified, such as the PpPEPCs, PpMDHs, PpPEPCKs, PpCSs, PpACLs, PpACOs, PpALMTs and PpVPs. The expression level of the PpCS2 is significantly correlated with the citric acid content. The expression level of the PpALMT1/4/6 is significantly correlated with the malic acid content. Interestingly, the PpTST1 is not only involved in the transport of sugar molecules, but is closely related to the accumulation of the organic acids in the fruit. In addition to structural genes, some transcription factors including the PpWRKYs, PpNACs, PpMYBs, PpMADSs, PpbZIPs, PpABREs and PpGRASs have been identified to involve in the metabolism of sugar and acid. The PpNAC1 and Pp-NAC5 activate the transcription of the PpGAD3 for the degradation of organic acid. The overexpression of the PpNAC050 significantly increases the content of fructose and glucose in the fruit. And it acts as a transcriptional suppressor to inhibit the expression of the vacuolar membrane monosaccharide exotransporter gene PpERDL16. The PpABRE1 binds directly to the promoter of the PpTST2 to activate its transcription. Morever, studies have found that the genetic background is internal factor affecting the fruit flavor. On chromosome 5, loci controlling the fruit sugar and acid trait have been identified. In adddition, the regulatory role of external factors has been not able to ignore. For example, spraying 150 μmol·L-1 melatonin on the leaves could significantly increase the contents of total soluble sugar and sucrose, increase the contents of glucose and sorbitol, and significantly decrease the contents of total organic acid, malic acid and citric acid in the fruits.1-MCP could delay the expression of malic acid and citric acid degrading genes in the fruit. The mechanism of sugar metabolism in the fruit under low temperature storage has been further studied, including those low temperature response genes, the PpZAT10, PpCBF6, PpRAP2.12, PpBZR1 and PpPGIP1, which change the sugar metabolism process by regulating the PpVAINV2 in the low temperature environment. The fruit thinning could affect the content of sugar components in the fruits by regulating the transcription levels of the PpSUT1 and PpSUT4 in the leaves.